WAYS OF ORGANIZING MONITORING OF MOTOR TRANSPORTATION - Abdurakhmanov Abdurashid; Khalmatov Misliddin Mukhammatovich (Galaxy International Interdisciplinary Research Journal, 2023)
The release of pollutants from vehicles and industrial enterprises into the atmosphere causes various diseases. Pollutants accumulate in brain tissue, skin, liver, pancreas, produce protein in urine and increase blood pressure. It causes lung edema, inflammation of the respiratory tract, disorders of the nervous and vascular system, eye damage and other diseases.